100% renewable energy policies in U.S. cities: strategies, recommendations, and implementation challenges. Issue 1 (1st January 2019) - Hess, David J.; Gentry, Haley
Abstract: Interviews and a survey were conducted with civil society advocates and government officials in U.S. cities and counties that have made a commitment to 100% clean, renewable, community-wide electricity. Survey questions indicated that the characteristics of the cities are consistent with the broader literature on policy adoption for urban sustainability and greenhouse-gas initiatives. For example, a majority of the communities in the sample indicated local concern with air and fossil-fuel pollution and climate-related risk, and they had a liberal (left-leaning) political culture. Policy "entrepreneurs" (initiative leaders) were from environmental organizations and/or the local government, and both often worked with a broad, community-wide coalition. The leading supportive frame other than greenhouse-gas emissions was local job creation, and the leading frame for opposition or skepticism was affordability. Recommendations and political strategy for advocates are discussed, and an analysis of implementation strategy is also provided. Some implementation plans also address affordability and equity for residential customers' energy needs.